Wind/WAVES Observations of Auroral Kilometric Radiation: Automated Burst Detection and Terrestrial Solar Wind ‐ Magnetosphere Coupling Effects. Issue 5 (6th May 2022) - Fogg, A. R.; Jackman, C. M.; Waters, J. E.; Bonnin, X.; Lamy, L.; Cecconi, B.; Issautier, K.; Louis, C. K.
Abstract: Auroral Kilometric Radiation (AKR) is the strongest terrestrial radio emission, and emanates from the same electron acceleration regions from which particles precipitate into the ionosphere, exciting the aurorae and other phenomena. As such, AKR is a barometer for the state of solar wind ‐ magnetosphere ‐ ionosphere coupling. AKR is anisotropically beamed in a hollow cone from a source region generally found at nightside local times, meaning that a single source region cannot be viewed from all local times in the magnetosphere. In radio data such as dynamic spectra, AKR is frequently observed simultaneously to other radio emissions which can have a similar intensity and frequency range, making it difficult to automatically detect. Building on a previously published pipeline to extract AKR emissions from Wind/WAVES data, in this paper a novel automated AKR burst detection technique is presented and applied to Wind/WAVES data. Over a five year interval, about 5000 AKR bursts are detected with median burst length ranging from about 30 to 60 min. During detected burst windows, higher solar wind velocity is observed, and the interplanetary magnetic field clock angle is observed to tend toward B Z  < 0, B Y  < 0, when compared with the entire statistical interval. Additionally, higher geomagnetic activity is observed during burst windows at polar, high and equatorial latitudes. Plain Language Summary: Auroral Kilometric Radiation (AKR) is a terrestrial radio emission which is excited by the same electrons which enhance the aurorae. Due to a combination of complex beaming, and the statistical position of the source region, an AKR event cannot be observed at all positions in the Earth's magnetosphere. A combination of different radio emissions are simultaneously observed in the radio data, including both AKR and non‐AKR sources. Building on previous work, in this paper individual AKR burst events are automatically detected from Wind/WAVES data over a five year interval. About 5000 events are detected over the interval, during which the observed geomagnetic activity was higher. Higher solar wind velocity and differences in the morphology of the interplanetary magnetic field are also observed during burst windows, both of which are known to excite magnetospheric dynamics. Key Points: A novel technique has been developed to detect individual Auroral Kilometric Radiation bursts in Wind/WAVES data When the technique is applied to 2000–2004 data, about 5000 bursts are detected with median duration 30–60 min During burst windows, higher solar wind velocity, more negative IMF B Z and greater geomagnetic activity is observed